MRGPRX2, atopic dermatitis, and red man syndrome - Azimi, Ehsan (Itch (Phila), 2017)
Vancoymycin causes red man syndrome, an itchy erythematous eruption involving the face, neck, and upper torso. Atopic dermatitis also manifests itch and erythema, and staphylococcus δ-toxin contributes to this process. The antibiotic and toxin each provoke mast cell degranulation but the mechanism had not been understood. We have determined that these compounds evoke degranulation via interaction with the same receptor, MRGPRX2, on mast cells. A receptor antagonist inhibits this process. Antagonists of this receptor may have therapeutic potential.